Physiological response to angling of Africa's premier freshwater angling species, the tigerfish Hydrocynus vittatus. Issue 2 (3rd April 2017) - Gerber, Ruan; Howatson, Glyn; Greenfield, Richard; Wagenaar, Ina; Smit, Nico
Abstract : Angling fraternities widely promote catch-and-release (C&R) as a fisheries management tool. This study aimed to determine the physiological response of Africa's premier freshwater angling species, the tigerfish Hydrocynus vittatus, to C&R angling in the Okavango Delta, Botswana. Standard angling techniques were used to collect fish, whereafter fish were anaesthetised in clove oil, blood drawn from the caudal vein and general biometric data noted, then revived and released. Blood plasma was analysed for glucose, cortisol and lactate concentrations to assess the effects of angling duration, fish size and fish condition. Larger fish were angled for a longer duration. Plasma glucose concentrations decreased with greater lactate concentrations, an indication of the aerobic and anaerobic work done during capture. Few individuals showed increased plasma cortisol concentrations. In extended-capture fish (angled for >1 min), lactate concentrations increased significantly above values for control fish. A linear regression analysis showed that well-fed fish had less of a stress response compared with less well-fed individuals. Furthermore, a discriminant function analysis indicated that the suite of biomarkers used were successful in indicating different stress responses according to angling duration. Angling and handling times along with nutritional status were likely influential factors in the range of glucose, cortisol and especially lactate levels in this study. These data suggest that C&R causes physiological stress to tigerfish, but could nonetheless be a valuable fisheries management tool, ensuring the sustainability of fish populations.